Renewable thermal energy sources : sediment and asphalt energy applications in an urban northern environment - Mäkiranta, Anne (Vaasan yliopisto, 2020)
This thesis evaluates if novel shallow geothermal energy, specifically geoenergy sources under sediment and asphalt layer, are viable and usable in Finnish climate conditions. The research consists of case studies implemented in two urban northern open-air study platforms: Suvilahti sediment heat installation and an asphalt energy field at the University of Vaasa (UVA) campus site. The usability of sediment heat is studied by long-term temperature measurements clarifying if sediment heat is annually renewable energy. Long-term temperature measurements are used also in the asphalt field to determine sufficiency of thermal energy in the ground. The research includes an estimation of available thermal energy from both urban heat energy sources. In total, the thesis includes seven published articles. Recovery of heat in the sediment layer during the summer was observed to be complete. The energy-saving ability of the sediment heat based low-energy network is also verified. Correct planning and sizing of the heat-collection network are considered important elements for the usability of sediment heat energy. With regard to the asphalt layer, results show there is sufficient thermal energy under the asphalt for utilization as a heat source. The average net heat ?ux density was measured at less than 15 % of the available irradiance due to the night time heat losses. Sediment heat is natural heat storage which is renewable and annually fully reloaded by the Sun. Asphalt heat is an appropriate heat source, even in higher latitude. Observed temperatures 0.5 m under the asphalt are positive from April to December. Asphalt is an urban geoenergy source which is a by-product of the built environment. The usability of asphalt heat could be increased by optimizing the ground structure for better conductivity of the surface and by daily collection and transfer of heat to seasonal storage.

Tämä väitöskirja arvioi, ovatko uudet geoenergialähteet sedimentistä ja asfaltin alta mahdollisia ja käyttökelpoisia Suomen ilmasto-olosuhteissa. Tutkimus koostuu tapaustutkimuksista, jotka on tehty kahdella kenttätutkimusalustalla pohjoisessa kaupunkiympäristössä: Suvilahden sedimenttilämpökohteessa ja asfalttienergiakentällä Vaasan yliopiston kampusalueella. Sedimenttilämmön käytettävyyttä on tutkittu pitkäaikaisilla lämpötilamittauksilla selvittäen, onko sedimenttilämpö vuosittain uusiutuvaa energiaa. Pitkäaikaisia lämpötilamittauksia on tehty myös asfalttikentällä, jotta voitaisiin määrittää lämpöenergian riittävyys hyödyntämistä varten. Tutkimus sisältää lämpöenergiamäärän arvion molempien urbaanien lämpöenergialähteiden osalta. Tähän väitöskirjaan on sisällytetty yhteensä seitsemän julkaistua artikkelia. Lämmön palautumisen havaittiin olevan täydellinen sedimenttikerroksessa kesän aikana. Sedimenttilämpöön perustuvan matalaenergiaverkoston energiansäästökyky todennettiin myös. Tarkoituksenmukaisen lämmönkeruuverkoston suunnittelun ja mitoituksen havaittiin olevan tärkeää sedimenttilämmön käytettävyydelle. Asfalttikerroksen osalta tulokset osoittavat, että asfaltin alla on riittävästi energiaa käytettäväksi lämmönlähteenä. Keskimääräisen nettolämpövuon mitattiin olevan vähemmän kuin 15 % saatavilla olevasta säteilyvoimakkuudesta yön aikaisten lämpöhäviöiden vuoksi. Merenpohjasedimentti on luonnollinen lämpövarasto, joka on uusiutuvaa ja vuosittain täysin auringon lataamaa energiaa. Asfalttilämpö on sopiva lämmönlähde, jopa pohjoisissa oloissa. Havaitut lämpötilat 0,5 m syvyydessä asfaltin alla ovat positiivisia huhtikuusta joulukuuhun. Asfaltti on urbaani geoenergialähde, joka on rakennetun ympäristön sivutuote. Asfalttilämmön käytettävyyttä voitaisiin lisätä optimoimalla maaperän rakennetta pinnan paremman lämmönjohtokyvyn aikaansaamiseksi ja päivittäisellä lämmön keräämisellä kausivarastoon.
Uusiutuvat lämpöenergialähteet : sedimentti- ja asfalttienergian sovellutukset urbaanissa pohjoisessa ympäristössä
Keywords: shallow geothermal energy; sediment heat; asphalt heat; distributed temperature sensing; heat energy; heat transfer; geothermal energy; heat pumps; renewable energy sources; fi=Energiatekniikka|en=Energy Technology|